Modulation of the Sensory Profile of Canned Sardinella lemuru in Balado Sauce by Pre-Cooking Techniques - Anis Khairunnisa; Ni Gusti Ayu Putu Intan Sri Wahyuni; Mahaldika Cesrany; Satiti Kawuri Putri; Nugraha, I Made Aditya (PUI BiGME Universitas Jambi, 2026)
Pre-cooking is an initial cooking stage in the processing of canned Sardinella lemuru (CSL) before the addition of sauce and sterilization, playing an essential role in determining product quality and sensory profile. This technique can influence attributes such as color, aroma, taste, and texture, making it a strategic effort for companies to maintain consistent quality, enhance consumer acceptance, and strengthen product competitiveness. This study aimed to evaluate consumer preference and the sensory profile of CSL in balado sauce using steaming (CSLS) and frying (CSLF) pre-cooking techniques at PT ICR. The samples used were meat from two types of canned Sardinella lemuru in balado sauce produced by PT ICR. The methods applied included a hedonic test to assess consumer preference and the Check-All-That-Apply (CATA) method to identify sensory attributes. Seven Quality Control staff participated in a Focus Group Discussion (FGD), while 30 production staff served as panelists for the hedonic and CATA tests. Hedonic data were analyzed using the Independent Sample T-Test with SPSS version 26, and CATA data were processed with XLSTAT 2021. Results showed that differences in pre-cooking techniques significantly affected taste and aroma (p<0.05) but had no significant effect on appearance and texture (p>0.05). The FGD identified 19 sensory attributes, including dark grey, cream, brownish yellow, light orange, dark brown, oily, garlic-like, fishy, metallic, salty, sweet, bitter, sour, umami, soft, dense, coarse, watery, and crumble. The ideal sensory profile was described as having umami and salty taste, fishy and oily aroma, dense yet tender texture, and brownish yellow color. Attributes influencing preference included cream color, watery, and crumble texture, while dark grey color was identified as a “Must Not Have” attribute that requires careful attention.